2007
DOI: 10.1590/s0103-64402007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Residual antibacterial activity of chlorhexidine digluconate and camphorated p-monochlorophenol in calcium hydroxide-based root canal dressings

Abstract: The purpose of this study was to evaluate the residual antibacterial activity of several calcium hydroxide [Ca(OH) 2 ]-based pastes, placed in root canals of dogs' teeth with induced chronic periapical lesions. Root canals were instrumented with the ProFile rotary system and filled with 4 pastes: G1 (n=16): Ca(OH) 2 paste + anesthetic solution; G2 (n=20): Calen ® paste + camphorated pmonochlorophenol (CMCP); G3 (n=18): Calen ® ; and G4 (n=18): Ca(OH) 2 paste + 2% chlorhexidine digluconate. After 21 days, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
18

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
0
7
0
18
Order By: Relevance
“…This methodology for inducing periapical lesions in dog's teeth has also been used in other studies (4,5,6,(8)(9)(10)(11)18), which reported that after contamination of the root canals by oral pathogens or inoculation of microorganisms from the endodontic microbiota, coronal sealing reduced the time necessary for formation of radiographically visible periapical lesions. Studies have shown that when the occlusal cavities are sealed, the periapical inflammatory reaction is usually induced within 60 days (4,6,8,11,13), whereas in the teeth without coronal sealing induction of periapical periodontitis occurs only after 180 days (7,12,15).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This methodology for inducing periapical lesions in dog's teeth has also been used in other studies (4,5,6,(8)(9)(10)(11)18), which reported that after contamination of the root canals by oral pathogens or inoculation of microorganisms from the endodontic microbiota, coronal sealing reduced the time necessary for formation of radiographically visible periapical lesions. Studies have shown that when the occlusal cavities are sealed, the periapical inflammatory reaction is usually induced within 60 days (4,6,8,11,13), whereas in the teeth without coronal sealing induction of periapical periodontitis occurs only after 180 days (7,12,15).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have been performed in dogs to evaluate the root canal treatment of teeth with periapical lesions (3)(4)(5)(6)(7)(8)(9) or incomplete root formation (10)(11) and the healing process after periapical surgery (12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Com o objetivo de potencializar o efeito antimicrobiano do Ca(OH) 2 , tem sido proposta, como medicação intracanal, a utilização da pasta de Ca(OH) 2 associada à CHX em concentrações de 0,12% a 2% (Evans et al, 2003;Sirén et al, 2004;Ercan et al, 2006;Soares et al, 2006a;Soares et al, 2007;Onçag et al, 2006;Manzur et al, 2007;Al-Nazhan e Al-Obaidae, 2008;Gomes et al, 2009b;Silva et al, 2009;Valera et al, 2009;2010;Delgado et al, 2010;Gondim et al, 2011;Lima et al, 2011). Essa associação resulta em um efeito antimicrobiano sinérgico (Evans et al, 2003;Podbielski et al, 2003;Zehnder et al, 2003;Zarella et al, 2005;Soares et al, 2007;Souza-Filho et al, 2008;Lima et al, 2011), sem alteração da solubilidade, alcalinidade ou atividade de ambas as substâncias (Podbielski et al, 2003;Basrani et al, 2003;Sirén et al, 2004;Signoretti et al, 2011).…”
Section: +unclassified
“…Essa associação resulta em um efeito antimicrobiano sinérgico (Evans et al, 2003;Podbielski et al, 2003;Zehnder et al, 2003;Zarella et al, 2005;Soares et al, 2007;Souza-Filho et al, 2008;Lima et al, 2011), sem alteração da solubilidade, alcalinidade ou atividade de ambas as substâncias (Podbielski et al, 2003;Basrani et al, 2003;Sirén et al, 2004;Signoretti et al, 2011). No entanto, não há consenso na literatura se a adição da CHX ao Ca(OH) 2 prejudica/altera a reação do tecido conjuntivo (Semenoff et al, 2008;Silva et al, 2009).…”
Section: +unclassified
See 1 more Smart Citation